Meningkatkan Perkembangan Motorik Halus pada Anak melalui Kegiatan Menganyam dengan Media Kertas Lipat - Riyadlotus Sholichah; Miftakhul Jannah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2020)
Early childhood education is a form of education that focuses on laying the foundation towards physical growth and development, especially on the fine motor skills of children. The purpose of this research is to describe the effect of weaving on the fine motor skills of early childhood group B in RA H Achmad Ali. This research uses a descriptive quantitative approach. The location of this research is RA H. Achmad Ali, Surabaya City. The subjects of this study were the children of group B RA H. Achmad Ali, Surabaya City with a total of 20 children. Based on the research that has been done, it is found that before the teacher's action is taken, the average fine motor skills are 50.3% which is in the very poor category. After the action in the first cycle, the average result of fine motor skills was 66.56%, which was in the poor category, this result increased compared to the pre-cycle results with an increase of 16.26%. The assessment in cycle II showed that the average fine motoric ability was 85% which was in the good category, this result increased by 18.44% compared to the first cycle which was in the poor category.